تحسين جودة الخدمة وأثرها على زيادة القدرة التنافسية للمنظمات دراسة ميدانية على مؤسسة الطيران العربية السورية - زاهر, بسام; صافيا, غزل (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتمثل الهدف من البحث في معرفة مستوى جودة الخدمات المقدمة في المؤسسة العربية السورية للطيران ومعرفة مدى رضا المسافرين عن تلك الخدمات وبيان مفهوم رضا العملاء وأهميته وأهدافه، وكذلك توضيح أهمية التركيز على العميل ودوره في تحقيق الميزة التنافسية في تقديم الخدمات وذلك في قطاع الطيران خاصة، والذي يمثل مجالاً للمنافسة بين شركات الطيران وبيان مدى مشاركة عاملي المؤسسة محل الدراسة في حرصهم على تجاوز توقعات العملاء وقدم البحث في النهاية ملخصاً لأهم النتائج التي تم التوصل إليها، كما قدم بعض المقترحات والتوصيات التي من شأنها زيادة القدرة التنافسية لمؤسسة الطيران العربية السورية, والارتقاء بها لتنافس على الصعيد العالمي. This Research aims at Knowing the quality level of the services provided by the Syrian Arab Airlines, Knowing the extent of the passengers' satisfaction with such services, and determining the concept of the clients' satisfaction, the importance of this concept and its target. The research clarifies as well the importance of concentrating on the client and his role in realizing the competition advantage in providing the services, particularly in flight sector where a competition exists among the Airlines, with showing the extent of the working staff(under study) contribution in their care to overpass the clients expectation. The research presented at the end a summary of the most important results that have been reached, and submitted some proposals and recommendations that will increase the Competitive Capacity of the Syrian Arab Airlines, upgrading it to compete globally.